Oxygen suffocation for firefighting in underground cavern - Yeo, Wei Liang (2016)
This study was conducted to investigate if maintaining a hypoxia environment (ambient oxygen volumetric concentration lower than the normal ambient condition of 21%) could eliminate the possibilities of fire ignition and fire development in a building. In practice, a hypoxia environment can be created and maintained by pumping in nitrogen to displace some of the air in the building. In this study, fire characteristics in a hypoxia environment (oxygen volumetric concentration of 15%) are investigated and compared to a normal environment by simulations using Fire Dynamic Simulator (FDS) and Pyrosim for an underground setting. 15% was chosen for the current study because it is the lower limit for occupational health impact according to OSHA [7]. Through analyzing research data, it shows that some common indoor materials (e.g., Polyurethane, PMMA, Normal and Fire-retarded plywood, ABS and Douglas fir wood) are still ignitable in a hypoxia environment. Using a spark igniter, radiating 50kW of heat flux, the material takes approximately 7s longer to ignite in hypoxia environment compared to normal environment (igniting at an average of 37s). With the decrease in oxygen concentration, the amount of soot and carbon monoxide generated from the combustion increases as well. Hence, shortening the available safe egress time (ASET) – the time duration between ignition and the building becomes untenable for occupants. In the simulation, setting a polyurethane chair (a very common piece of furniture) on fire, the heat release rate (HRR) and temperature reading directly above the fire source (Device 8, XYZ = 10m,40m,3m) in hypoxia environment are lowered at 2900 kW and 700ºC, respectively, compared to 4000 kW and 850ºC, respectively, in normal environment. Soot generation rate in hypoxia environment is 0.01 kg/kgfuel, about twice as much as the normal environment (kg/kgfuel). The amount of CO concentration reading taken from Device 8 at 15% (700 PPM) was 28% more than at 21% (500 PPM) oxygen concentration environment. Decrease in oxygen concentration lowers the HRR and temperature but could increase in soot and CO generations, which are undesirable. Inhalation of soot and CO would result in health impact like headache or nausea within 1 hour of exposure, and life threatening or death within 2-3 hours of exposure. This study showed that some common indoor materials are still ignitable in hypoxia environment and the fire can still develop. With lowered oxygen concentration, larger amount of soot and CO would be generated compared to normal environment, leading to health and evacuation concerns. Therefore, much consideration should be made in installation of hypoxia system for an underground facility.